Purple hearts [videorecording (DVD)] - Furie, Sidney J.; Furie, Sidney J.; Furie, Sidney J.; Wahl, Ken, 1954-; Ladd, Cheryl (Archive collection., 2009)
A drama of love and courage set against the fierce background of a war that U.S. history keeps trying to sweep out of sight. Navy nurse Deborah Solomon is the girl that Jardian finds in his moment of greatest despair. She's the first thing about Vietnam that makes any sense to him and he'll do anything to be with her. So Jardian breaks the soldier's prime rule of survival--he volunteers.